Lesbian Cartography of Galician Poetry. Two Pioneers: María do Carme Kruckenberg and María Xosé Queizán - Suárez Briones, Beatriz (Madrygal. Revista de Estudios Gallegos, 2023)
This article is an exercise in lesbian criticism of two collections of poems by two lesbian writers: María do Carme Kruckenberg (Vigo, 1926-2015) and María Xosé Queizán (Vigo, 1936). The two books have the same axis, the love and desire of a woman; they are books in which a female subject in love writes words of love and desire to a you who is loved and desired. So far the similarities between both texts; the fundamental divergence, which this work will seek to make sense of, is that in Kruckenberg’s text the gender of that you is carefully hidden, while in Queizán’s you is another woman, without any veiling or ambiguity. This lesbian critique proposal of lesbian reading or lesbianizing reading uses two different strategies: on the one hand, “biomythography”, learned from Audre Lorde and, on the other hand, it responds to Monique Wittig’s call to recover women’s history, erased by heteropatriarchy: remembering, and when remembering is impossible, inventing. Lesbian criticism always functions as a hermeneutics of suspicion. In addition, this article tries to explain and adequately assess the different textual strategies used by the authors, which cover the path that goes from the silenced and encrypted of Carme Kruckenberg to the explicit and celebratory of María Xosé Queizán. Formally, this research it also goes to the work of Hélène Cixous to propose white ink as (a) model of writing the body and lesbian desire.